2020
DOI: 10.1186/s12199-020-00897-y
|View full text |Cite
|
Sign up to set email alerts
|

Occupational exposures to blood and body fluids among healthcare workers in Ethiopia: a systematic review and meta-analysis

Abstract: Background Occupational exposure to blood and body fluids is a major risk factor for the transmission of blood-borne infections to healthcare workers. There are several primary studies in Ethiopia yet they might not be at the national level to quantify the extent of occupational blood and body fluid exposures (splash of blood or other body fluids into the eyes, nose, or mouth) or blood contact with non-intact skin among the healthcare workers. This systematic review and meta-analysis aimed to estimate the pool… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 36 publications
(75 reference statements)
0
33
0
Order By: Relevance
“…NSI-related risk factors have not yet been properly identified in Iran. Studies have identified factors such as excessive and unnecessary injections, poor personnel training, female gender, high workloads, and excessive fatigue especially at nighttime as the most important causes of NSI [ 7 , 12 17 ]. Moreover, a systematic review found age, level of education, number of shifts per month, and history of training courses for individuals as factors influencing NSI.…”
Section: Introductionmentioning
confidence: 99%
“…NSI-related risk factors have not yet been properly identified in Iran. Studies have identified factors such as excessive and unnecessary injections, poor personnel training, female gender, high workloads, and excessive fatigue especially at nighttime as the most important causes of NSI [ 7 , 12 17 ]. Moreover, a systematic review found age, level of education, number of shifts per month, and history of training courses for individuals as factors influencing NSI.…”
Section: Introductionmentioning
confidence: 99%
“…Giving patients care without PPE can also reduce nurses' concentration during activities, which can lead to anxiety and further exposure to blood and body uids. (15,18,20).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, in Ethiopia, a lack of reports exists to quantify the pooled prevalence of exposures to BBFs among health care workers (HCWs). Moreover, the epidemiology of blood-borne infections in Ethiopia has been on the rise and dynamically changing over the past decades, along with poor compliance with standard precautions among HCWs (15).…”
Section: Introductionmentioning
confidence: 99%
“…A total of 377 forms were distributed and completed by the respondents. The form contained detailed information regarding the research description, roles of respondents, and in 2 million infected with HBV and 170,000 with HIV (Sahiledengle et al, 2020). A study in a hospital in the Adara district showed that the prevalence of splashes of blood or body fluids from patients was 28%, and these were experienced by healthcare workers assisting births and operations; in addition, officers who washed the linen were also at double risk of being splashed with patients' body fluids (Kaweti & Abegaz, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…Other research also showed a similar finding that the face is a common area of exposure to body fluids. Healthcare workers reported that they generally had splashes from patients' body fluids in the eye area, while others reported fluids in the mouth and nose areas (Kasatpibal et al, 2016;Kaweti & Abegaz, 2017;Sahiledengle et al, 2020).…”
Section: Methodsmentioning
confidence: 99%